The role of waterways in promoting urban resilience: The case of Kochi City - Zeba Aziz; Indro Ray; Sandeep Paul (Indian Council for Research on International Economic Relations (ICRIER), 2018)
Coastal cities around the world are locales of high vulnerability. The issues are graver in the developing world where the challenges posed by the urbanisation and climate change multiply the existing risks. Here, we examine the case of Kochi, an Indian city located at the centre of a rapidly urbanizing coastal and estuarine region. In Kochi, a port city characterised by crisscrossing canals and rivers connected to a backwater system, waterways used to play a major role in the socio-economic and cultural development of the region. They not only supported the commerce and economy but also connected communities, supported a rich and diverse ecosystem and provided livelihood opportunities. However, poor planning and management of the industrialization and urbanization processes resulted in the neglect and widespread exploitation of this resource over the years, undermining its ability to support both ecology and connectivity. In the recent years, partly due to growing recognition of climate change, and need for both mitigation and adaptation, there has been a renewed interest in investing in waterways to enhance connectivity in the region. The study examines how water ways can promote the climate, social and economic resilience of the city. It also critically compares these efforts against the global experiences and attempts to identify multiple limitations and challenges to development of water ways in Kochi. The global experiences could be useful for Kochi as it is now starting to focus on waterways development as a crucial part of its integrated transportation network.
Keywords: R40; R42; R58; Q25; 330; Inland waterways; Resilience; Kochi; Climate change